Extension of depth-resolved reconstruction of attenuation coefficients in optical coherence tomography for slim samples - Hohmann, Martin; Lengenfelder, Benjamin; Kanawade, Rajesh; Klämpfl, Florian; Schmidt, Michael (Optical Coherence Tomography 2, 2015)
Coherent light propagating through turbid media is attenuated due to scattering and absorption. The decrease of the intensity of the coherent light is described by the attenuation coefficient. The measured decay of the coherent light through turbid media with optical coherence tomography (OCT) can be used to reconstruct the attenuation coefficient. Since most of the OCT systems work in the near-infrared region, they are the optical window from 800-1400 nm in tissue. Hence, the most part of the attenuation coefficient is caused due to the scattering. Therefore, deriving the attenuation coefficient is one way to get an approximation of the scattering coefficient which is difficult to access even up to day. Moreover, OCT measurements are one of the few possibilities to derive physical properties with micrometre resolution of the media under investigation.
Keywords: OCT; Optical Coherence Tomography; attenuation coefficent; reconstruction